Pengaruh Kompetensi, Pengembangan Karir, dan Pemberian Reward terhadap Produktivitas Kerja Karyawan pada PT Megahputra Sejahtera Cabang Palopo - Ramdani Ramdani; Tanti Tanti; Fani Nahda Widayah; Erwina Erwina; Ris Akril Nurmansjah (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to analyze the influence of competence, career development, and rewards on employee productivity at PT Megahputra Sejahtera, Palopo Branch. A quantitative approach was employed using a survey method. The data used included both primary data, collected through questionnaires, and secondary data from company documentation. The sampling technique used was saturated sampling, involving a total of 30 employee respondents. The data analysis methods consisted of descriptive analysis to describe the respondent profiles, validity and reliability tests to ensure the quality of the research instrument, and classical assumption tests such as normality, multicollinearity, and heteroscedasticity tests to confirm data suitability. The main analytical tool used was multiple linear regression to examine the effect of the independent variables on the dependent variable, namely employee productivity. The research findings indicate that simultaneously, competence, career development, and rewards have a significant effect on employee productivity. This is supported by the F-test results, which show a significance level below 0.05. However, when tested partially, only the reward variable showed a positive and significant effect on employee productivity. The competence and career development variables did not have a statistically significant effect when assessed individually. These results suggest that the company’s reward system plays a key role in motivating employees and enhancing their performance. On the other hand, the existing competence and career development programs may not be effectively implemented or aligned with employees' actual needs and expectations, hence failing to significantly impact productivity. Based on these findings, it is recommended that PT Megahputra Sejahtera continues to strengthen its reward system by ensuring it is fair, motivating, and performance-based. Furthermore, the company should improve its career development strategies and competence-building initiatives to be more structured, goal-oriented, and relevant to employee development pathways. This dual approach can help foster a more productive and engaged workforce.